Differential Weight Loss with Intermittent Fasting or Daily Calorie Restriction in Low- and High-Fitness Phenotypes - Davis, Ashley E. (Exp Physiol, 2021)
Recent interest has focused on the benefits of time-restricted feeding strategies, including intermittent fasting, for weight loss. It is unsettled, however, if intermittent fasting is more effective than daily caloric restriction at stimulating weight loss, and how each is subject to individual differences. Here, rat models of leanness and obesity, artificially selected for intrinsically high (HCR) and low (LCR) aerobic capacity, were subjected to intermittent fasting and 50% calorie restrictive diets in two separate experiments using male rats. The lean, high-fitness HCR and obesity-prone, low-fitness LCR rats underwent 50% calorie restriction while body weight and composition were monitored. The low-fitness LCR rats were better able to retain lean mass than the high fitness HCR, without significantly different proportional loss of weight or fat. In a separate experiment using intermittent fasting in male HCR and LCR rats, alternate-day fasting induced significantly greater loss of weight and fat mass in LCR compared to HCR rats, even though HCR had a more marked reduction in ad-libitum day food intake. Altogether, this suggests that intermittent fasting is an effective weight loss strategy for those with low intrinsic aerobic fitness, however, direct comparison of caloric restriction and intermittent fasting is warranted to determine any differential effects on energy expenditure in lean and obesity-prone phenotypes.